Situation Report: Poland, 7 April 1984 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The National Party Conference Party Documents Assessed / by Ewa Celt Poland's Alienated Youth Foreign Trade: Performance and Prospects Polish Moslem Congress Held in Bialystok Sundry Items